AB0236 DIFFERENCES AND DETERMINANTS OF PHYSICIAN'S AND PATIENT'S PERCEPTION IN GLOBAL ASSESSMENT OF RHEUMATOID ARTHRITIS. (2nd June 2020) - Azevedo, S.; Guimarães, F.; Almeida, D.; Faria, D.; Silva, J.; Rodrigues, J.; Peixoto, D.; Alcino, S.; Tavares-Costa, J.; Afonso, C.; Teixeira, F.
Abstract : Background: Patient's Global Assessment of Disease Activity (PtGA) and Physician's Global Assessment of Disease Activity (PhGA) are assessed as part of commonly used measures of disease activity in RA. 1 Both are important measures in treat-to-target strategies in Rheumatoid Arthritis (RA), but often provide discordant results. 2, 3 This can provide an erroneous assessment of disease activity in patients under Biologic treatment and mislead treatment decisions, namely switches. Objectives: To assess differences and determinants of PtGA and PhGA in RA patients under biologic treatment. Methods: Cross-sectional study, including 46 patients with RA diagnosed according to the ACR/EULAR criteria, under biologic treatment, consecutively evaluated in day-care unit. Participants completed patient-reported outcomes (PROs), including PtGA, and sociodemographic characteristics. Physicians collected comorbidities and parameters of inflammatory activity (erythrocyte sedimentation rate [ESR] and C-reactive protein [CRP]) and completed PhGA and disease activity score 28 with ESR (DAS28). SPSS was used for statistical analysis and significance level was defined as 2-sided p<0.05. Results: Clinical and laboratory characteristics of patients are shown in table 1. PtGA and PhGA were significantly different (36.1±27.6 mm vs 8.7±14.2 mm, p< 0.001) and a positive discordance (PtGA>PhGA, more than 25mm in visual analogue scale [VAS]) was found in 54.3% of cases. PtGA had a correlation with PROs (Pain VAS, 36-Item Short Form Health Survey [SF-36], Health Assessment Questionnaire [HAQ], Functional Assessment of Chronic Illness Therapy [FACIT], EuroQol [EQ5D] and Hospital Anxiety and Depression Scale [HADS]), CRP, tender and swollen joint counts and an association with comorbidities like fibromyalgia or osteoarthritis (OA). No association was found between PtGA and age, sex, education level, profession, employment status, extra-articular manifestations, positivity of rheumatoid factor, ESR, years of disease evolution or number of biologic treatments. In multivariable analyse including SF-36, CRP, tender joints count and OA (R 2 adjusted= 0.672), the main predictors of PtGA were lower SF36, concomitant OA and higher CRP level. PhGA had a correlation with PtGA, pain VAS, CRP, tender and swollen joints. No association was found between PhGA and patient or physician age, patient or physician sex, extra-articular manifestations, positivity of rheumatoid factor, ESR level, years of disease evolution or number of biologic treatments. In multivariable analysis including ESR, tender and swollen joints count and CRP (R 2 adjusted= .800), the main predictors of PhGA were swollen joint count and higher CRP level. Conclusion: This study showed the variability implied on global assessment of RA activity. Overall PtGA is based on function and also in subjective and emotional experience of pain, whereas the PhGA is based on more objective measures, more related to disease activity. References: [1]Kanekoa Y. et al, Determinants of Patient's Global Assessment of Disease Activity and Physician's Global Assessment of Disease Activity in patients with rheumatoid arthritis: A post hoc analysis of overall and Japanese results from phase 3 clinical trials. Modern Rheumatology 2018; 28(6):960–967 [2]Furu M. et al. Discordance and accordance between patient's and physician's assessments in rheumatoid arthritis. Scand J Rheumatol. 2014; 43(4):291-5. Ann Rheum Dis. 2016 Sep;75(9):1661-6. doi: 10.1136/annrheumdis-2015-208251. Epub 2015 Oct 22. [3]Portier A. et al, Patient-perceived flares in rheumatoid arthritis: A sub-analysis of the STRASS treatment tapering strategy trial. Joint Bone Spine . 2017; 84(5):577-581 Disclosure of Interests: None declared